1997
DOI: 10.1182/blood.v89.10.3663
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitor Antibody Response Is More Complex in Hemophilia A Patients Than in Most Nonhemophiliacs With Factor VIII Autoantibodies

Abstract: Approximately 25% of hemophilia A patients infused with factor VIII (fVIII) mount an immune response, which leads to its inactivation. Anti-fVIII autoantibodies are also seen rarely in individuals with normal fVIII. We have previously demonstrated that some anti-A2 and anti-C2 domain antibodies are fVIII inhibitors and that many patients have additional inhibitors with a fVIII light chain (LCh) epitope outside C2. Because the contribution of the different antibodies to the plasma inhibitor titer had been exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
111
1
7

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(135 citation statements)
references
References 22 publications
16
111
1
7
Order By: Relevance
“…We could not examine IgG 1 antibodies because of non-specific binding reactions, but it was supposed that the FVIII antibody seen in the present case was an inhibitor that inhibited the FVIII activity mainly via light chain recognition. This finding matches the report by Prescot et al [22]. In convalescent phase, only IgG 4 antibody was detected by the ELISA method and IgG 4 antibody recognized mainly heavy chains in immunoblotting analysis, although its inhibitor activity was unclear.…”
Section: Discussionsupporting
confidence: 92%
“…We could not examine IgG 1 antibodies because of non-specific binding reactions, but it was supposed that the FVIII antibody seen in the present case was an inhibitor that inhibited the FVIII activity mainly via light chain recognition. This finding matches the report by Prescot et al [22]. In convalescent phase, only IgG 4 antibody was detected by the ELISA method and IgG 4 antibody recognized mainly heavy chains in immunoblotting analysis, although its inhibitor activity was unclear.…”
Section: Discussionsupporting
confidence: 92%
“…This suggests different mechanisms of inhibitor formation, which is expected given that inhibitors are a consequence of an alloimmune response in congenital haemophilia A patients and an autoimmune response in acquired haemophilia patients. This finding is also consistent with the observation that inhibitor-binding epitopes in congenital and acquired haemophilia patients may differ [26].…”
Section: The Role Of Regulatory T Cells In the Pathogenesis Of Fviii supporting
confidence: 92%
“…There was no data to differentiate the exact fraction of their findings that recognized a3 from those that recognized A3-C1. Human antibodies directed to the a1 region are rare, occurring only at an incidence of 1´8±7% (Fulcher et al, 1987;Lubahn et al, 1989;Scandella et al, 1989;Prescott et al, 1997). We found 14´3% (4 out of 28) for a1, which is the highest number reported; however, explanations for this high incidence are not clear.…”
Section: Discussionmentioning
confidence: 59%
“…Using a synthetic peptide of residues 1687±1695 in competitive RIA (radioimmunoassay), Tiarks et al (1992) reported a 46% (38 out of 82) positive rate for a3 occurring in patients with haemophilia A. Prescott et al (1997) reported a 29% positive rate for spontaneous inhibitors, recognizing an epitope of a broader region of a3-A3-C1. There was no data to differentiate the exact fraction of their findings that recognized a3 from those that recognized A3-C1.…”
Section: Discussionmentioning
confidence: 99%